How can we bridge the gap between literacy and health in South Sudan? - China Mayol Kuot (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2019)
Addressing the low literacy rates in South Sudan has been a longstanding priority for primary health care providers as a way to improve the country's poor overall health status. Improving the literacy rate by "ensuring that all girls and boys complete primary and secondary education" by 2030 is ambitious but achievable for optimum health and socio-economic development. While general literacy is an important determinant of health, it is not sufficient to address the major health challenges facing the South Sudanese population. Effective health education at primary health care points can help ensure healthy lives while other sectors are improving literacy.